The Education of Children in an Islamic Family in the Digital Era - Ihsan, Muhammad Zidan Nur; Inayati, Nurul Latifatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The rapid development of the times has significantly impacted all lines of life, including the family. This can be seen from technology development such as smartphones, televisions, computers, and others. Children in today's generation cannot be separated from the digital world, such as FB, Instagram, Twitter, WhatsApp, and others. All of these developments will not be separated from negative impacts, one example is the erosion of Islamic values in social circles, especially for children. Seeing this phenomenon, equipping a child with Islamic education or values is very important. So that it can reduce and even take advantage of the advancement of current technology. In addition to reducing the impact of the digital era, Islamic education also shapes children into righteous and righteous children. This article explains the impact of digitalization in education and how family education is in the digital era. In this article, the author tries to explain the impact that children receive in the digital era and how Islamic education is in the digital era. The research method in this article is qualitative, with a literature study approach. The purpose of this article is to discuss in full the positive and negative impacts of technological developments and explain how to educate children from the perspective of Islam.